HISTORY AND ONTOLOGY OF RHETORIC OF THE GREEK PERIOD - Melly, Melly Gunawan; Putri Misri Fani; Salsabila Kania Rahma (Rahis Cendekia Indonesia, 2024)
The study of rhetoric in ancient Greece reveals a complex interplay between the history and ontology of rhetoric. The main focus is on the development of rhetoric as a communication practice and its influence on philosophical and political thought at the time. This study highlights the important role of rhetoric in the formation of Greek individual and social identities, as well as the construction of their social reality. By analyzing classical texts and historical documents, this study explores how rhetoric was used to strengthen and influence public decisions and shape worldviews. Through an ontological approach, this study also explores the basic concepts of truth, justice, and morality that underlie rhetorical practices at the time. Thus, a historical and ontological understanding of Greek rhetoric provides deep insights into the relationship between language, power, and truth in the context of ancient culture.